Analisis Potensi Wisata Bahari Berbasis Sistem Informasi Geografis di Pantai Langala Provinsi Gorontalo - La Ode Juni Akbar; Daud Yusuf; Muhammad Kasim (Universitas Negeri Gorontalo, 2019)
The research aimed to investigate the maritime tourism potential of Langala Beach. The research was conducted in Dulupi Sub-District, Boalemo Regency, Gorontalo Province. The geographical location of the research area is 000 30 04